Comparison of off-clamp microwave scissors-based sutureless partial nephrectomy versus on-clamp conventional partial nephrectomy in a canine model - Nguyen, Ha Ngoc; Yamada, Atsushi; Naka, Shigeyuki; Mukaisho, Ken-Ichi; Tani, Tohru (Frontiers in Surgery, 2023)
Objectives: To compare the usefulness and safety of off-clamp microwave scissors-based sutureless partial nephrectomy (MSPN) with on-clamp conventional partial nephrectomy (cPN) in dogs. Methods: We performed off-clamp MSPN using microwave scissors (MWS) in six dogs, and on-clamp cPN in three dogs, in two-stage experiments. The bilateral kidney upper poles were resected via a midline incision under general anesthesia. After 14 days of follow-up, the lower pole resections were performed. The renal calyces exposed during renal resections were sealed and transected using MWS in off-clamp MSPN and were sutured in on-clamp cPN. In the off-clamp MSPN group, the generator’s power output of MWS was set as either 50 W or 60 W for each kidney side. We compared the procedure time (PT), ischemic time (IT), blood loss (BL), and normal nephron loss (NNL) between the two techniques using the Mann-Whitney U test. Results: We successfully performed 24 off-clamp MSPNs and 12 on-clamp cPNs. The off-clamp MSPN was significantly superior to on-clamp cPN in avoiding renal ischemia (median IT, 0 min vs. 8.6 min, p < 0.001) and reducing PT (median PT, 5.8 min vs. 11.5 min, p < 0.001) and NNL (median NNL, 5.3 mm vs. 6.0 mm, p = 0.006) with comparable BL (median BL, 20.9 mL vs. 23.2 mL, p = 0.804). No bleeding and major urine leakage were noted during the reoperations. Conclusions: Off-clamp MSPN outperforms on-clamp cPN in lowering the risks of postoperative renal function impairment in dogs.